60.7k views
25 votes
Please help me with this please

Please help me with this please-example-1
User Lith
by
5.7k points

1 Answer

8 votes

Answer:

x = 12√2

y = 12√2

Explanation:

By applying cosine rule in the given triangle,

cos(45)° =
\frac{\text{Adjacent side}}{\text{Hypotenuse}}


(1)/(√(2))=(y)/(24)

y =
(24)/(√(2))

y =
12√(2)

By applying sine rule in the given triangle,

sin(45°) =
\frac{\text{Opposite side}}{\text{Hypotenuse}}


(1)/(√(2))=(x)/(24)

x =
(24)/(√(2))

x =
12√(2)

User Tostao
by
5.8k points